Integration of Sales Digitalization and Financial Reporting of MSMEs: A Qualitative Study in North Sulawesi - Eliska Gricy Lumempouw; Pingkan Elni Wowor; Christania Graciella Angel; Debora Helen Rompas (Cattleya Darmaya Fortuna, 2026)
This study explores the integration of digital sales platforms with financial reporting practices among Micro, Small, and Medium Enterprises (MSMEs) in North Sulawesi. While platforms such as Shopee, TikTok Shop, and Instagram have boosted sales, many MSMEs still rely on manual bookkeeping that does not align with Indonesian Financial Accounting Standards for MSMEs (PSAK EMKM). Using a qualitative descriptive approach, data were collected through semi-structured interviews with MSME owners in Manado. The findings indicate that although digitalisation has expanded market reach and increased revenues, MSMEs face difficulties in translating online transactions into reliable financial statements. Respondents also highlighted the need for government support in providing integrated infrastructure that connects digital sales and financial reporting. The study underscores the importance of policies that combine digital marketing with accounting literacy, supported by incentives and simplified applications. It contributes theoretically by addressing the underexplored link between digitalisation and MSME accounting, while offering practical implications for policymakers and business practitioners.